The Ideas of Boys and Girls About the Future and the Results of the State Final Certification - N.P. Shilova (Психолого-педагогические исследования)
The research described in the article is devoted to the study of the relationship between the ideas of boys and girls about their future and the results they received on the unified state exam (USE). A two-stage study was conducted, during which the meaningful elements of predicting the future of the participants were first identified, and then these data were compared with the educational achievements of the respondents. The study sample consisted of 150 people aged 18 to 28 years. At the first stage, the I.S. Cohn methodology "I am in five years" was used, at the second stage, the respondents were presented with the results of the first stage and asked questions about their achievements. The study showed that boys and girls who received high results on the Unified State Exam more often used the words "I know" and "I will do" in their ideas about the future. A connection was found between the grades obtained on the Unified State Exam and the assessment of satisfaction with one's achievements. Boys and girls who passed the exam with high scores rate the achievement of their plans lower than those who passed the exam with a lower score. The lack of achievements with high scores obtained on the Unified State Exam is associated by respondents with changed circumstances or lack of time, and with good results – with strict adherence to plans. The results obtained can be useful in practical work with modern boys and girls when discussing plans for the future with them.